What Did We Learn From Current Progress in Heat Stress Tolerance in Plants? Can Microbes Be a Solution? - Ahmad, Muhammad; Imtiaz, Muhammad; Shoib Nawaz, Muhammad; Mubeen, Fathia; Imran, Asma (Frontiers in Plant Science, 2022)
Temperature is a significant parameter in agriculture since it controls seed germination and plant growth. Global warming has resulted in an irregular rise in temperature posing a serious threat to the growth and yield of various cropsagricultural production around the world. Plants need a precise temperature at a right time for normal growth. A slight rise increase in temperature acts as stress and impacts all growth stages of the crop. Heat stress hasand exert an overall negative impact on different developmental stages including plant phenology, development, cellular activities, gene expression, anatomical features, the functional and structural orientation of leaves, twigs, roots, and shoots. It These impacts ultimately decreases the overall biomass, affect reproductive process, decrease total number of flowersing and fruits fruiting resulting inand significant yield losses. Plants have inherent mechanisms to cope with different stressors including heat that which may vary depending upon the type of from plant species and type, duration, and degree of the heat stress. Plants initially adapt adapt avoidance and then tolerance strategies to combat heat stress. The tolerance pathway involves ion transporter, osmoprotectants, antioxidants, heat shock protein which help the plants to survive under heat stress. To develop heat-tolerant plants using above-mentioned strategies requires a lot of time, expertise and resources. Despite, all theseOn contrary, plant growth-promoting rhizobacteria (PGPRs) is a cost-effective, time-saving and environmentuser-friendly approach to support and enhance agricultural production under a range of environmental and stressed conditions including stresses. PGPR produce and regulate various phytohormones, enzymes, and metabolites that help plant to maintain growth under heat stress. They form a biofilm, reduce decrease abscisic acid, stimulate root development, enhance heat shock proteins, deamination of ACC enzyme, and increase siderophores and nutrient availability especially nitrogen and phosphorous. In spite of Despite extensive work done on plant heat stress tolerance in general, very few comprehensive reviews are available on the subject especially the role of microbes for plant heat tolerance. This article reviews the studies on the retaliation, adaptation, and tolerance to heat stress at different levels, explains approaches, sheds light on how microbes can help to induce heat stress tolerance in plants.